Pengembangan Buku Penuntun Praktikum Perubahan Iklim dengan Model Argument-Driven Inquiry (ADI) - Susi Ulfah; Neni Hasnunidah; Arwin Achmad (Universitas Lampung, 2018)
A practical guidebook was needed to support the laboratory activities. This study aims to describe the characteristics, validity, and practicality guidebook. The design of this study was Research and Development (R D) with 4-D models define, design, develope, and disseminate. However, this research was only up to the develop stage. Product that was developed in this study was colored, with the interesting picture, and used tahoma letter, font was 12. Each worksheet of the guidebook consists of student identity, lab work title, theory, objections, reasearch question, tools dan materials, work steps, argument schemes, argument sessions, and Reports. Expert and practitioner validation results showed the category